Novel coronavirus: A Pandemic Situation in Nepal - Bhat, Deepmala Rana (Europasian Journal of Medical Sciences, 2020)
A novel coronavirus (2019-nCoV) has spread out rapidly from Wuhan, Hubei Province, China and has been spreading to other provinces and countries and has become pandemic. The COVID-19 infection spreads through droplets of saliva or nasal discharge when an infected individual coughs or sniffles. The common symptoms shown are fever, cough, fatigue and pneumonia. The total coronavirus cases are 21,357,711and 763,381 deaths have been reported worldwide as of Aug 15, 2020. The total cases in Nepal has reached to 25,551 with total recovered cases of 17,077 and 99 deaths in total as of Aug 14, 2020. In Nepal, different parts of the country are in lockdown where individuals remain at home aside from emergency situations.